Changes In Astigmatisma Before And After Pterygium Surgery At Undaan Eye Hospital, Surabaya - Eko Dian Hs; Agus Priyanto; Achmad Parjiko Adji Sanjaya (Kirana Publisher (KNPub), 2022)
Pterygium is a common external ocular disease with a prevalence ranging between 0.7% and 33% globally. The disease is described as a wing-shaped, fibrovascular lesion that traverses the nasal or temporal limbs. This study aims to determine changes in astigmatism before and after pterygium surgery at the Undaan Eye Hospital in Surabaya. The population in this study were all pterygium sufferers who had changes in astigmatism before and after surgery at the Undaan Eye Hospital Polyclinic, Surabaya. The sample of 47 people was selected using probability sampling with the type